2015
DOI: 10.1037/xlm0000102
|View full text |Cite
|
Sign up to set email alerts
|

Representation of item position in immediate serial recall: Evidence from intrusion errors.

Abstract: In immediate serial recall, participants are asked to recall novel sequences of items in the correct order. Theories of the representations and processes required for this task differ in how order information is maintained; some have argued that order is represented through item-to-item associations, while others have argued that each item is coded for its position in a sequence, with position being defined either by distance from the start of the sequence, or by distance from both the start and the end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…Given these findings, the observation of overall lower performance for the serial order STM tasks in the aphasic group relative to the control group may be less surprising. Recent theoretical work has suggested that serial order information in the verbal domain may be coded at multiple representational levels, including updating of bindings directly between language item representations, and linking of items to distinct, non-linguistic positional markers (Fischer-Baum & McCloskey, 2015). With respect to both theoretical accounts, and especially relative to the within-language domain binding account, the important implication of the present study is that processes involved in item and serial order retention reflect distinct cognitive capacities and hence are separable, even when operating within the language domain.…”
Section: Group Versus Single Case Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these findings, the observation of overall lower performance for the serial order STM tasks in the aphasic group relative to the control group may be less surprising. Recent theoretical work has suggested that serial order information in the verbal domain may be coded at multiple representational levels, including updating of bindings directly between language item representations, and linking of items to distinct, non-linguistic positional markers (Fischer-Baum & McCloskey, 2015). With respect to both theoretical accounts, and especially relative to the within-language domain binding account, the important implication of the present study is that processes involved in item and serial order retention reflect distinct cognitive capacities and hence are separable, even when operating within the language domain.…”
Section: Group Versus Single Case Analysesmentioning
confidence: 99%
“…Fischer-Baum and McCloskey (2015) showed that serial order STM failures can be accounted for by inefficient positional markers, but also by deficient inter-item associations, the latter process considering that serial position information is directly encoded via the updating of inter-item connections. Given that items are considered by many models of STM to be coded by the language system, this would mean that serial order information can also be encoded directly within the language system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in sequences like ABCD, this mechanism retains that A came first, that D came last, and that B and C had some position relative to the first and last one (for reviews, see e.g. Fischer-Baum et al, 2011;Fischer-Baum & McCloskey, 2015;Henson, 1998).…”
Section: Is a Sensitivity To Sequence-edges Domain-general?mentioning
confidence: 99%
“…Moreover, item recall is more influenced by linguistic knowledge than order recall (see for example Saint‐Aubin and Poirier []). More recent work suggests that serial order information can be processed using different codes such as item‐to‐item association, or start‐anchored or end‐anchored position (see for example Fischer‐Baum and McCloskey []) or depending on their rhythm in spoken sequences [Hartley et al, ], and, finally, recall of temporal order information is more accurate with congruent spatial order information [Fischer‐Baum and Benjamin, ]. All these different codes for serial information could depend on different neural substrates, although this does not seem an economical solution.…”
Section: Introductionmentioning
confidence: 99%